MR Findings of a Primary Intramedullary Malignant Melanoma: Case Report and Literature Review - Farrokh, Dordaneh; Fransen, Patrick; Faverly, Daniel (American Journal of Neuroradiology, 2001)
Summary: A case of primary malignant melanoma of the conus medullaris depicted at MR imaging is presented. Tumoral histoimmunologic analysis revealed features of malignant melanoma. Because findings for primary melanoma outside the spinal cord were negative, the diagnosis of primary intramedullary malignant melanoma was established. This rare tumor should be suspected when T1-weighted images show signal hyperintensity and T2-weighted images show signal iso- or hypointensity, with mild contrast enhancement of the lesion. However, these features may vary depending on intratumoral bleeding and melanin content.